Analisis Strategi Guru dalam Meningkatkan Kemampuan Membaca Permulaan di Kelas 1 SD Bala Keselamatan Palu : Analysis of Teacher Strategies in Improving Beginning Reading Skills in Grade 1 of Palu Salvation Army Elementary School - Fatmilia Werangalu; Yun Ratna Lagandesa; Muhammad Aqil; Rangga Putera Boroallo; Rizal Rizal (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2026)
This study aims to describe the strategies a teacher employs to enhance the early reading skills of first-grade students at SD Bala Keselamatan Palu and to identify the factors that support and hinder their implementation. A qualitative descriptive approach was adopted, involving a first-grade teacher and 28 students (14 boys and 14 girls) as subjects. Data were collected through observation, interviews, and documentation, and subsequently analysed using the Miles and Huberman interactive model, which encompasses data collection, data reduction, data display, and conclusion drawing. Data validity was ensured through technique and source triangulation. The results indicate that the teacher implemented differentiated instruction using a "flexible grouping" strategy as the primary method to improve students' early reading skills. This strategy began with identifying students' initial abilities, followed by grouping them based on proficiency levels and learning readiness; adjustments were made regarding materials, methods, media, and task difficulty for each group, complemented by individual guidance, supplementary instruction outside regular class hours, and continuous evaluation to update group assignments. The strategy's success was supported by teacher competence, the availability of learning media and facilities, student motivation, school support, and parental cooperation. Conversely, challenges included significant disparities in students' reading abilities, limited instructional time, a lack of family support at home, low self-confidence among some students, and the dynamics of adjusting group compositions. The findings demonstrate that differentiated instruction via flexible grouping effectively accommodates diverse student abilities and fosters greater improvement in early reading skills than uniform, whole-class instruction. These findings offer practical insights for teachers in designing adaptive and sustainable reading instruction.